Blockchain Technology-based Used in Carnival Creative Industry: An Empowerment Tool for Carnival Industry Players on the Internet of Value Era - Abdul Muhsyi; Hari Sukarno; N. Ari Subagio; Khanifatul Khusna; Agus Priyono (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
The creative economy in Indonesia is increasingly boosting the national economy, as evidenced by the success of events like the Jember Fashion Carnaval (JFC) and Banyuwangi Ethno Carnival (BEC), but industry players still need to utilize blockchain technology in the Internet of Value era to create economic value. Annually held in Jember, East Java, the Jember Fashion Carnival showcases extravagant costumes and parade performances, while the BEC, an ethnic carnival in Banyuwangi, celebrates the cultural diversity of the region through traditional dances and costumes. The purpose of this research is to identify readiness for implementing blockchain technology, identify the strengths of EFAS in the blockchain technology-based carnival creative industry, explore the uniqueness of blockchain technology-based carnival innovative products, and formulate a blockchain technology-oriented strategic plan in the carnival creative industry. This research is exploratory in nature, utilizing analytical methods such as TRA and TAM. The research results indicate that blockchain technology can serve as a valuable alternative tool in the era of the internet, particularly for the carnival industry, which includes events such as BEC and JFC. The community's lack of understanding of blockchain technology and NFTs poses the biggest threat. The carnival industry requires risk mitigation and education to ensure successful implementation. We can carry out this effort by providing assistance to carnival industry players, enabling them to enhance their competitiveness and seize potential external opportunities. The research shows that JFC and BEC are not yet fully ready to adopt blockchain in organizing Carnival events, but there is a strong intention and positive attitude towards implementing blockchain. The successful implementation of blockchain requires technical assistance and the building of human resource capacity.